2021
DOI: 10.1093/geronb/gbab096
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Internet Adoption in Early and Advanced Old Age: Does Internet Self-Efficacy Matter?

Abstract: Objectives Understanding why older adults (including those in very old age) use or do not use the Internet can build on the technology acceptance model (TAM). In this cross-sectional study, we translate the TAM to the Internet and assume that perceived usefulness of the Internet (PUI) and perceived ease of use of the Internet (PEUI) will be revealed as major predictors of behavioural intention to use the Internet (BII). Additionally, we consider the role of Internet self-efficacy (ISE) as ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
6
0
3
Order By: Relevance
“…This finding confirms the current body of knowledge (Kim & Kim, 2004;Lai, 2014;Hew et al, 2015;Kim et al, 2006;Bi & Kim, 2020;Lu et al, 2011;Raman, 2019;Khadir, Ravindranath, & Sen, 2021;Ozturk et al, 2021;Hatamifar, Ghaderi, & Nikjoo, 2021;Tak & Gupta, 2021;Medeiros et al, 2022). In terms of technological self-efficacy, the finding of this paper also supported previous research (Hasan, 2006;Rahman, Ko, Warren, & Carpenter, 2016;Latikka, Turja, & Oksanen, 2019;Wilkowska, Heek, & Ziefle, 2021;and Jokisch et al, 2021). As can be seen, the findings of the study not only support the literature but also add conceptual value with the tested model.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding confirms the current body of knowledge (Kim & Kim, 2004;Lai, 2014;Hew et al, 2015;Kim et al, 2006;Bi & Kim, 2020;Lu et al, 2011;Raman, 2019;Khadir, Ravindranath, & Sen, 2021;Ozturk et al, 2021;Hatamifar, Ghaderi, & Nikjoo, 2021;Tak & Gupta, 2021;Medeiros et al, 2022). In terms of technological self-efficacy, the finding of this paper also supported previous research (Hasan, 2006;Rahman, Ko, Warren, & Carpenter, 2016;Latikka, Turja, & Oksanen, 2019;Wilkowska, Heek, & Ziefle, 2021;and Jokisch et al, 2021). As can be seen, the findings of the study not only support the literature but also add conceptual value with the tested model.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of Wilkowska, Heek, and Ziefle (2021) showed that technological self-efficacy significantly affected the user acceptance of lifelogging technologies. Jokisch et al (2021) found that technological self-efficacy was a major factor in older adults' Internet use. Accordingly, the hypothesis relating to technological self-efficacy is as follows:…”
Section: Technological Self-efficacymentioning
confidence: 99%
“…Studies addressing empirical evidence related to the TAM with old and very old adults are rare, as are studies with an explicit focus on digital health services ( 10 ). However, there is evidence that associations of the TAM change with increasing age ( 11 ). In the “young-old” age between 60 and 75 years, when many resources are still available for most individuals, perceived usefulness has been shown to be crucial.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, after introducing ICTs to older adults, many reported improved independence and autonomy ( Straka and Clark, 2000 ; White et al, 2010 ; Bobillier Chaumon et al, 2013 ; Pimentel et al, 2016 ); self-esteem and ICT self-efficacy ( Billipp, 2001 ; Woodward et al, 2010 ; Bobillier Chaumon et al, 2013 ; Tsai et al, 2015 ; Pimentel et al, 2016 ). It is of great importance that older adults believe in their capacity to use ICTs, a hallmark of self-efficacy, as it is a predictor for both mid-term and long-term ICT adoption and use ( Czaja et al, 2006 ; Mitzner et al, 2019 ; Jokisch et al, 2021 ). One study identified the significance of age in relation to ICT and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%